E-learning for management and marketing in libraries E-formation pour le marketing et le management des bibliotheques / edite par Daisy McAdam. - IFLA Satellite Meeting (2003 Geneva, Switzerland); McAdam, Daisy; Gale Group; International Federation of Library Associations (Munchen K.G. Saur, 2005)
"These contributions to a conference held in Geneva in 2003 focus on the very latest approaches to ""e-Learning."" The power and enormous diversity of this medium become apparent as experts from all over the world compare notes and raise a whole new range of issues. The reader can examine the presentations of the various practitioners or go straight to the discussions at the end for insight into what the future holds for teachers and students alike."
Remerciements/ acknowledgements -- Preface/ Preface -- Introduction -- Critical issues related to internet teaching -- De l'apprenant au concepteur: Vers la mise en place d'une formation continue a distance des bibliothecaires/ Documentalistes en tunisie -- Les formations au management utilisant les nte a l'ensibb: Analyse transversale et retours d'experience -- The growth of e-learning in marketing education and its implications for librarians -- La dimension europeenne de l'information a l'information des personnels enseignants: Presentation du site web "acceder a l'information scientifique et technique", espace d'autoformation dedie a l'enseignement du primaire europeen -- Remerciements/ acknowledgements -- Calis, computer-assisted learning tool, didacticiel d'apprentissage d'une methodologie de recherche documentaire developpe dans le cadre du campus virtuel Suisse -- Une communaute virtuelle d'apprentissage en gestion de projet -- La formation a distance dans un contexte sud-sud: Defis et enjeux -- Teaching smart: Developing reusable instructional modules on the web -- Formation initiale et formation continue: Les outils pedagogiques en ligne proposes par le service commun de documentation de l'universite de nice sophia-antipolis -- Developing e-learning prototype for library management: a case study -- Synthese -- Detailed programme of the two days -- List of speakers + short biography.
Papers presented at the IFLA Satellite Meeting, Section Management and Marketing, Management & Meeting Section, Geneva Switzerland, July 28-30, 2003.
Articles in English and French.
Electronic reproduction.
Keywords: Distance education; Internet in education; Libraries -- Marketing -- Congressses; Electronic books